2023
DOI: 10.1371/journal.pone.0278404
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and determinants of private health insurance enrollment in a country with heavily subsidised public healthcare: A cross-sectional survey in East Coast Malaysia

Abstract: Malaysia’s subsidised public healthcare system is heavily reliant on government funding. Increasing the uptake of private health insurance (PHI) would alleviate the financial burden on public healthcare facilities caused by high patient loads. The study aimed to determine the uptake of PHI and its associated factors among the East Coast Malaysian populations. A cross-sectional online survey was conducted between February and June 2021. Proportionate stratified sampling was applied to select 1138 participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Our study also observed that health status generally was not significantly associated with OOP expenditure, perhaps indicating that Malaysia’s heavily subsidized healthcare system did confer adequate financial risk protection to the population for inpatient care ( Chua and Cheah, 2012 ). In addition, the determinants of PHI ownership status found in our study, which was not our main interest, were comparable to other studies conducted in Malaysia ( Balqis-Ali et al ., 2021 ; Al-Sanaani et al ., 2022 ; Abd Khalim et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also observed that health status generally was not significantly associated with OOP expenditure, perhaps indicating that Malaysia’s heavily subsidized healthcare system did confer adequate financial risk protection to the population for inpatient care ( Chua and Cheah, 2012 ). In addition, the determinants of PHI ownership status found in our study, which was not our main interest, were comparable to other studies conducted in Malaysia ( Balqis-Ali et al ., 2021 ; Al-Sanaani et al ., 2022 ; Abd Khalim et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The private health sector is recognized as an important player in any health system, but many policymakers do not know the extent of its strengths and limitations. In some countries, efforts by the public sector to collaborate with private providers face political constraints, but there are many other opportunities for maximizing the sector to help improve public health [16]. Private insurance caters to several chronic diseases and can help to reduce the burden of personal medical expenses for policyholders [17].…”
Section: The Private Sector As An Under-utilized Entitymentioning
confidence: 99%